MENINGKATKAN KOMPETENSI GURU DALAM PENGELOLAAN KELAS MELALUI SUPERVISI KUNJUNGAN KELAS DI SMP N 4 PASAMAN - Hartasani Hartasani (STKIP Pesisir Selatan, 2017)
Abstract This type of research is action research. According to Zuriah, (2003: 54) action research emphasizes the activities (action) by testing an idea into practice. Action research conducted is a school action research (PTS). This school action research consists of four stages in each cycle. Among them: 1) planning, 2) action, 3) observer, and 4) reflection. Based on the results of research and discussion that has been stated in the previous chapter, it can be concluded that the supervision of class visits can improve the competence of teachers in managing the class at SMP N 4 Pasaman Pasaman Barat. This can be seen from the competence of teachers in managing the class in SMP N 4 Pasaman Pasaman Barat district that has increased. The average competence of teachers in managing the class at SMP N 4 Pasaman Regency Pasaman Barat in cycle I is 73.02 (enough). This average is increased in cycle II with an average of 82.02 (good). Thereby Improving Teacher Competence in Classroom Management through Supervision of Class Visit at State Junior High School 4 Pasaman Pasaman Barat Regency can be improved through the supervision of class visit. Keywords: Teacher Competency, Classroom Management, Class Visiting Supervision